Ivan Grozny volcano (Iturup Island, Kuril Islands): material composition of eruption products and current activity - R.V. Zharkov; O.V. Bergal-Kuvikas; A.V. Degterev; F.A. Romanyuk; S.E. Borisovsky (Вестник Камчатской региональной ассоциации "Учебно-научный центр". Серия: Науки о Земле, 2024)
The paper presents summary data on the historical activity of Ivan Grozny volcano (Iturup Island, Kuril Islands), including the results of our own studies of solfatar-hydrothermal and eruptive activity of the volcano since 2004. Using modern analytical methods, we obtained data on the chemical composition of the volcano rocks and pyroclastics of the explosive eruption in 2012–2013. The composition of the volcano rocks varies from andesites to daciandesites of medium potassium series. Pyroclastics of the 2012–2013 eruption corresponds to andesites with medium potassium content in terms of bulk chemical composition. The material composition of glasses according to microprobe data is much more acidic. The obtained values are similar to the geochemical compositions of the products of the 1973 and 1989 eruptions. Taking into account the prevailing wind regime dominating in the central part of Iturup Island, the hazard from ash fall of probable future eruptions of Ivan Grozny volcano was assessed, indicating the predominant spread of ash in the north-western, western and south-western directions.